Navigating the AI Landscape: Sectoral Insights on Integration and Impact - Saxena, Ashish K (Engineering International, 2024)
This study delves into the varied sentiments and attitudes prevalent across the different sectors related to integrating Artificial intelligence (AI). Understanding how sectors perceive and embrace these changes is crucial for informed decision-making and policy formulation as AI technologies continue to thrive in industries. Artificial intelligence is making waves in 2023 as businesses, consumers, and the government benefit from this technology, promising new opportunities, economic growth, and the transformation of different industries. There was so much propaganda surrounding artificial intelligence based on economic factors such as employment, education, income patterns, housing, and food security, and with time, these issues have been proven true or false. AI will have a broadly beneficial effect on society.